2012
DOI: 10.1620/tjem.226.59
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Ligands for Natural Killer Cell Activating Receptors in Colon Carcinoma

Abstract: Natural killer (NK) cells play important roles in the immune defense against tumor cells. The function of NK cells is determined by a balance between activating and inhibitory signals. DNAX accessory molecule-1 (DNAM-1) and NK group 2 member D (NKG2D) are major NK cell activating receptors, which transduce activating signals after binding their ligands CD155, CD112 and major histocompatibility complex class I-related chains A and B (MICA/B). However, the expression and functions of these ligands in colon carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
(54 reference statements)
0
20
1
3
Order By: Relevance
“…20,29,32,37,[41][42][43] NKG2D ligands are often upregulated on a wide range of tumor cells in response to cellular stress during malignant transformation. However, as tumors progress, soluble MICA/B or ULBPs are often shed from the membranes of tumor cells.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…20,29,32,37,[41][42][43] NKG2D ligands are often upregulated on a wide range of tumor cells in response to cellular stress during malignant transformation. However, as tumors progress, soluble MICA/B or ULBPs are often shed from the membranes of tumor cells.…”
Section: Nk Receptors In Tumorsmentioning
confidence: 99%
“…Since the expression of MICA molecules is associated with stress-induced factors, their increased expression can be induced by viral or bacterial infection. MICA expression is observed in many epithelial cell-derived tumors such as colon cancer, breast cancer, and lung cancer (Vallian et al, 2012;Zhang et al, 2012;Chen et al, 2013), and on the surface of some melanoma cells. Renal cancer cells also express MICA (Qiu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of DNAM1 has been reported in breast cancer, CRC, AML, and melanoma [17,18,37,53] and in melanoma, it has been shown that tumor-associated ibroblasts (TAF) by modulating the surface expression of DNAM-1 based on cell-to-cell interactions could inhibit NK cell function [54]. Also, DNAM1 ligand CD155 upregulation on multiple myeloma (MM) cells has been reported and resulted in increased sensitivity to NK cell-mediated lysis [55].…”
Section: Stimulatory Nectin-binding Adhesion Moleculementioning
confidence: 99%